2002
DOI: 10.1068/p3167
|View full text |Cite
|
Sign up to set email alerts
|

Visual Feature Binding in Early Infancy

Abstract: How does the developing brain of the human infant solve the feature-binding problem when visual stimuli consisting of multiple colored objects are presented? A habituation--dishabituation procedure revealed that 1-month-old infants have the ability to discriminate changes in the conjunction of a familiar shape and color in two objects. However, this good earlier performance was followed by poorer performance at 2 months of age. The performance improved again at 3 months of age. Detailed analysis of the oculomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…Other infant research has looked in more detail at feature binding per se. For example, infants as young as 1 month of age will dishabituate to situations in which a green triangle and a yellow ring emerge from a momentary period of occlusion as a yellow triangle and a green ringömaintaining all of the same features, changing only their bindings (eg Bushnell and Roder 1985;Kaldy and Leslie 2003;Slater et al 1991;Taga et al 2002).…”
Section: Research On Feature Bindingmentioning
confidence: 98%
“…Other infant research has looked in more detail at feature binding per se. For example, infants as young as 1 month of age will dishabituate to situations in which a green triangle and a yellow ring emerge from a momentary period of occlusion as a yellow triangle and a green ringömaintaining all of the same features, changing only their bindings (eg Bushnell and Roder 1985;Kaldy and Leslie 2003;Slater et al 1991;Taga et al 2002).…”
Section: Research On Feature Bindingmentioning
confidence: 98%
“…Previous behavioral studies indicated that visual abilities such as color discrimination (Morrone et al, 1993), directional discrimination (Wattam-Bell, 1996), stereopsis (Birch et al, 1982;Braddick et al, 1983), and oculomotor control (Taga et al, 2002) increase drastically around 3 months of age. Based on these findings, we anticipate that functional response patterns of the cortex during visual perception may also change at around this age.…”
Section: Introductionmentioning
confidence: 97%
“…The subsequent recovery by 4–6 months of age can be interpreted as an establishment of coordination between the two systems. U-shaped changes in a given behavior have been observed in reaching (Butterworth, 1989 ) and cross-modal orientation (Taga et al, 2002 ). The developmental organization of these circuits is a complex process that begins at early gestational age (Kostovic et al, 1995 ) and continues until adulthood.…”
Section: Introductionmentioning
confidence: 99%